GLACIOLOGICAL RESEARCH PROGRAM IN EAST QUEEN MAUD LAND, EAST ANTARCTICA PART 4,1984 - FUJII, Yoshiyuki; KAWADA, Kunio; YOSHIDA, Minoru; MATSUMOTO, Shinichi (National Institute of Polar Research, 1986)
P(論文) departmental bulletin paper